Alat Pemberi Pakan Ikan Lele Dalam Drum Otomatis Berdasarkan Usia dan Jumlah Ikan Dengan Metode Fuzzy Logic - Arif, Setia Yusuful; Tamami, Niam; Madyono, Madyono (Majalah Ilmiah Teknologi Elektro, 2023)
Abstract — The trend for consumption fish consumption continues to increase rapidly, even the Food and Agriculture Organization (FAO), says fish cultivation output is expected to increase by around 172 million tonnes in 2021. Therefore efforts are needed to increase national catfish production. New methods of cultivating catfish have emerged, one of which is the method of cultivating catfish in drums. However, there are still many catfish breeders in drums in Indonesia who still use conventional methods which are no longer effective, because many catfish seeds die before maturity, this is due, among other things, to unscheduled feeding and the amount of feed weight that is inaccurate with the amount and the age of the fish in a drum which causes the growth of catfish to be less than optimal. Based on these problems, it is encouraging to develop a tool that can control and monitor fish feeding schedules and the total weight of fish feed according to the number and age of fish in one drum based on a microcontroller by utilizing the fuzzy logic method which can facilitate the process of reasoning in language. (linguistic reasoning), and only by means of a smartphone, farmers can set feeding schedules and choose the number of fish and the age of the fish in a drum. The result is that the tool is able to provide feed according to the feed schedule with an error rate of 0%, and the tool can provide feed according to the feed dosage with an accuracy of up to 98.9% with an average accuracy of 96.09%. Keywords— Automatic Fish Feeder, MQTT Dashboard,  Fuzzy Logic